Population density and antibiotic resistant of bacteria from bivalve perna viridis and anadara granosa - Asmat Ahmad,; Nur Diana Mehat,; Rahimi Hamid,; Gires Usup, (Universiti Kebangsaan Malaysia, 2014)
This study was carried out to know the bacteria population density in the blood cockle (Anadara granosa) and green lipped mussel (Perna viridis), to analyse the bacteria resistance towards antibiotics and antimicrobial activity of isolates against selected pathogen. Samples of blood cockle and green lipped mussel were obtained from five areas in Kedah and Negeri Sembilan. Bacterial population densities in mussels and cockles were 3 × 102 – 8 × 108 CFU/mL and 5 × 102 – 5 × 108 CFU/mL, respectively. A total of 162 isolates were obtained, of which 131 isolates were from mussels and 31 isolates were from cockles. Vibrio sp. was the most dominant genus in both types of samples. Antibiotic testing of all isolates showed most were resistant to Penicillin (10 U) and most were sensitive to Ciprofloxacin (5 μg). Most isolates (160/162) showed resistance to at least two antibiotics and 10 isolates were resistant to more than five antibiotics. Multiple antibiotic resistance indices (MAR) were calculated based on the antibiotic resistance results. Most isolates had a MAR index value of 0.2 which indicated the isolates were not contaminated with antibiotic residues. The highest index value was 0.7. Fifteen out of 39 isolates which produced beta-lactamase enzyme were tested for antimicrobial activity against selected pathogen. Results indicated that antimicrobial activity were varies among the isolates. Isolate SMII-Ip produced antimicrobial activity against six out of the nine tested pathogen and none of the isolates active against Pseudomonas mirabilis.